2009
DOI: 10.1007/s11524-009-9406-z
|View full text |Cite
|
Sign up to set email alerts
|

Aging and Urbanization: The Neighborhood Perception and Functional Performance of Elderly Persons in Belo Horizonte Metropolitan Area—Brazil

Abstract: Currently, half of the world population resides in cities. The percentage of world population that is elderly is expected to double from 11% to 22% by 2050 and will be concentrated in urban areas of developing countries. The purpose of this study was to evaluate the functional status of elderly who live in the Belo Horizonte Metropolitan Area, Minas Gerais State, Brazil. The International Classification of Functioning, Disability and Health (ICF) was employed as the theoretical model. Probabilistic sampling wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
26
1
14

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(49 citation statements)
references
References 36 publications
5
26
1
14
Order By: Relevance
“…These associations persisted after adjusting for social and demographic characteristics, health status, and other indicators of social relations. Older age, female gender, and number of comorbidities also showed independent associations with the presence of limitations in performing one or more ADL, corroborating other studies 15,26 . However, the associations between target characteristics and the number of ADL performed with limitations were less evident in the current analysis, limited to female gender, lack of children, and dissatisfaction/indifference towards personal relations.…”
Section: Discussionsupporting
confidence: 88%
“…These associations persisted after adjusting for social and demographic characteristics, health status, and other indicators of social relations. Older age, female gender, and number of comorbidities also showed independent associations with the presence of limitations in performing one or more ADL, corroborating other studies 15,26 . However, the associations between target characteristics and the number of ADL performed with limitations were less evident in the current analysis, limited to female gender, lack of children, and dissatisfaction/indifference towards personal relations.…”
Section: Discussionsupporting
confidence: 88%
“…In the cities of Denmark, the indicators of social capital significantly associated with the disability were the diversity in social relations, the social participation, and the social support 27 . In Brazil, Ferreira et al 28 observed that only the component called perception of the physical environment was associated with the functional disability of elderly in the RMBH, Minas Gerais.…”
Section: Discussionmentioning
confidence: 99%
“…A total of 15 ADL were evaluated, of which eight are considered basic ADL (getting out of bed, eating, combing one's hair or brushing one's teeth or washing one's face, walking from one room to another at the same level, bathing, dressing, toileting and cutting the nails of one's feet) and the remaining seven are classified as instrumental ADL (climbing ten steps, taking medication, walking two or three blocks, going out shopping, preparing one's own meal, taking a bus and undertaking household chores). These ADL have been validated and used in studies with elderly populations in Brazil 2,25,26,27 .…”
Section: Study Variablesmentioning
confidence: 99%
“…The characteristics of the environment within which people live, or neighborhood characteristics, can potentially influence a person's functional performance, especially the functional performance of elderly people, who have in the neighborhood the main, or even the only, diameter of living space 1,2 . Defining functional performance as what a person does in the current or usual environment 3 , neighborhood characteristics may influence the functional performance of elderly people by facilitating or by hindering their engagement in activities and participation in daily life 1,3,4 .…”
Section: Introductionmentioning
confidence: 99%